Ethnomathematics study: revealing mathematical aspects in determination of a good daily activities in indigenous societies of paseban and cikondang west java - I Muhafidin; E Nurlaelah; E Sudihartinih (Pascasarjana Universitas Pendidikan Indonesia, 2018)
This study is an attempt to show the relationship between culture and mathematics. Students’ paradigm nowadays considers that Mathematics is an abstract concept; as a result they do not like the subject. In fact, indirectly within a culture or group. The aim of the study is to determine the existence of mathematical aspects in determining a good day of daily activities in indigenous societies of Paseban and Cikondang villages. This study uses a qualitative approach with ethnography method such as observation, interviews, documentation, and field notes. The research is conducted in two places namely Paseban Tri Panca Tunggal Cigugur Village, District Cigugur, Kuningan regency, West Java and Cikondang, Lamajang Village, District Pangalengan, Bandung regency, West Java. The results of the study show that there is the presence of mathematical aspects in determining good day of daily activities in indigenous societies of Paseban and Cikondang villages. This study recommends that mathematics is closely related to culture due to the existence of ethnomathematics.